Rodzina naturalna a rodzina zastępcza. Pojęcia, podobieństwa i różnice - Walancik-Ryba, Karolina (Studia Edukacyjne, 2020)
Walancik-Ryba Karolina, Rodzina naturalna a rodzina zastępcza. Pojęcia, podobieństwa i różnice [Natural Family and Foster Family. Concepts, Similarities and Differences]. Studia Edukacyjne nr 56, 2020, Poznań 2020, pp. 297-307. Adam Mickiewicz University Press. ISSN 1233-6688. DOI: 10.14746/se.2020.56.16 The article “Natural Family and Foster Family. Concepts, Similarities and Differences” covers the problem of defining the terms: the family and the foster family. The author compares these concepts, focusing on the similarities and differences between the two. Based on the issues related to these concepts, she attempts to define the concept of the foster family.